Myeloid-derived interleukin-1β drives oncogenic KRAS-NF-κΒ addiction in malignant pleural effusion - Marazioti, A; Lilis, I; Vreka, M; Apostolopoulou, H; Kalogeropoulou, A; Giopanou, I; Giotopoulou, G; Krontira, A; Iliopoulou, M; Kanellakis, N; Agalioti, T; Giannou, A; et al. (Nature Publishing Group, 2018)
Malignant pleural effusion (MPE) is a frequent metastatic manifestation of human cancers. While we previously identified KRAS mutations as molecular culprits of MPE formation, the underlying mechanism remained unknown. Here, we determine that non-canonical IKKα-RelB pathway activation of KRAS-mutant tumor cells mediates MPE development and this is fueled by host-provided interleukin IL-1β. Indeed, IKKα is required for the MPE-competence of KRAS-mutant tumor cells by activating non-canonical NF-κB signaling. IL-1β fuels addiction of mutant KRAS to IKKα resulting in increased CXCL1 secretion that fosters MPE-associated inflammation. Importantly, IL-1β-mediated NF-κB induction in KRAS-mutant tumor cells, as well as their resulting MPE-competence, can only be blocked by co-inhibition of both KRAS and IKKα, a strategy that overcomes drug resistance to individual treatments. Hence we show that mutant KRAS facilitates IKKα-mediated responsiveness of tumor cells to host IL-1β, thereby establishing a host-to-tumor signaling circuit that culminates in inflammatory MPE development and drug resistance.